b)
|2x+6|+|6x-42|≤0
|2x+6|+|6x-42|=0
|2x+6|=0
2x+6=0
2(x+3)=0
x+3=0⇒x=-3
|6x-42|=0
6x-42=0
6(x-7)=0
x-7=0⇒x=7
x∈{-3,7}
c)
|x²+5x|+|y²-y|≤0
|x²+5x|+|y²-y|=0
|x²+5x|=0
x²+5x=0
x(x+5)=0
I. x=0
II. x+5=0⇒x=-5
x∈{0,-5}
|y²-y|=0
y²-y=0
y²=y |:y
y=1
x∈{1}
d)
|x²-7x|+|y²+4y|≤0
|x²-7x|+|y²+4y|=0
|x²-7x|=0
x²-7x=0
x(x-7)=0
I. x=0
II. x-7=0⇒x=7
x∈{0,7}
|y²+4y|-0
y²+4y=0
y(y+4)=0
I. y=0
II. y+4=0⇒y=-4
y∈{0,-4}
e)
|x+2|+|y-7|≤1
|x+2|+|y-7|∈{0,1}
1. |x+2|+|y-7|=0
|x+2|=0
x+2=0⇒x=-2
|y-7|=0
y-7=0⇒y=7
2. |x+2|+|y-7|=1
I. |x+2|=1
x+2∈{1,-1} |-2
x∈{-1,-3}
|y-7|=0
y-7=0⇒y=7
II. |x+2|=0
x+2=0⇒x=-2
|y-7|=1
y-7∈{1,-1} |+7
y∈{8,6}
f)
|3x-2|+|-15x+10|≤0
|3x-2|+|-15x+10|=0
|3x-2|=0
3x-2=0
3x=2⇒x=2/3
|-15x+10|=0
-15x+10=0 |:5
-3x+2=0
-3x=-2 |·(-1)
3x=2⇒x=2/3